Health-promoting and preventive interventions for community-dwelling older people published from inception to 2019: a scoping review to guide decision making in a Swedish municipality context - Saranda Bajraktari; Marlene Sandlund; Magnus Zingmark (BMC, 2020)
Abstract Background Despite the promising evidence of health-promoting and preventive interventions for maintaining health among older people, not all interventions can be implemented due to limited resources. Due to the variation of content in the interventions and the breadth of outcomes used to evaluate effects in such interventions, comparisons are difficult and the choice of which interventions to implement is challenging. Therefore, more information, beyond effects, is needed to guide decision-makers. The aim of this review was to investigate, to what degree factors important for decision-making have been reported in the existing health-promoting and preventive interventions literature for community-dwelling older people in the Nordic countries. Methods This review was guided by the PRISMA-ScR checklist (Preferred Reporting Items for Systematic reviews and Meta-Analysis extension for Scoping Reviews), the methodological steps for scoping reviews described in the Arksey and O'Malley's framework, and the Medical Research Council's (MRC) guidance on complex interventions. Eligible studies for inclusion were randomised controlled trials (RCTs) concerning health promotion or primary prevention for community-dwelling older people implemented in the Nordic countries. Additionally, all included RCTs were searched for related papers that were reporting on additional factors. Eligible studies were searched in seven databases: PubMed, SCOPUS, CINAHL, Academic Search Elite, PsycINFO, SocINDEX, and SPORTDiscus. Results Eighty-two studies met the inclusion criteria (twenty-seven unique studies and fifty-five related studies). Twelve studies focused on fall prevention, eleven had a health-promoting approach, and four studies focused on preventing disability. All interventions, besides one, reported positive effects on at least one health outcome. Three studies reported data on cost-effectiveness, three on experiences of participants and two conducted feasibility studies. Only one intervention, reported information on all seven factors. Conclusions All identified studies on health-promoting and preventive interventions for older people evaluated in the Nordic countries report positive effects although the magnitude of effects and number of follow-ups differed substantially. Overall, there was a general lack of studies on feasibility, cost-effectiveness, and experiences of participants, thus, limiting the basis for decision making. Considering all reported factors, promising candidates to be recommended for implementation in a Nordic municipality context are 'Senior meetings', 'preventive home visits' and 'exercise interventions' on its own or combined with other components.